Formulation and Evaluation of Sustained Release Sumatriptan Mucoadhesive Intranasal in-Situ Gel - alkufi, hussein K.; Kassab, Hanan J. (Iraqi Journal of Pharmaceutical Sciences, 2019)
Sumatriptan(ST) is a selective agonist at serotonin 5-HTI receptors, as well as 5-HT1B/1D subtypes. It is effective for acute migraine attacks, but has a short half life (about 2 hours) and low oral bioavailability (15%). The purpose of this study was to develop and optimize nasal mucoadhesive in-situ gel(IG) of ST to enhance nasal residence time for migraine management. Cold method was used to prepare different formulas of ST nasal IG, using thermosensitive polymers (poloxamer 407 alone or with poloxamer 188) with a mucoadhesive polymer hyaluronic acid (HA) which were examined for gelation temperature and gelation time, pH, drug content, gel strength, spreadability, mucoadhesive force determination, viscosity, in-vitro drug release, and the selected formula was subjected to fourier transform infrared (FTIR) compatibility studies, and to ex-vivo permeation study, histological evaluation of the sheep mucosal tissue after ST nasal gel application for 6 hours.The results showed that the formula IG7 prepared from poloxamer 407(19%), poloxamer188 (4%) and HA (0.5%) had an optimum gelation temperature (32.66±1.52°C), gel strength (43.66± 1.52 sec), mucoadhesive force (8067.93± 746.45dyne2), in-vitro drug release (95.98%) over 6h, ex-vivo permeation study (89.6%) during the 6 h. study with no histological or pathological change in the nasal sheep tissue and no interaction between drug and other additives in IG7. Formulation of ST as a nasal insitu gel to avoid first pass metabolism and ease of administration coupled with less frequent and sustained drug release, will enhance patient compliance.